Conjugated microporous polymer based on star-shaped triphenylamine-benzene structure with improved electrochemical performances as the organic cathode material of Li-ion battery. (1st October 2018) - Chen, Zhangxin; Li, Weijun; Dai, Yuyu; Xu, Ning; Su, Chang; Liu, Junlei; Zhang, Cheng
Abstract: Based on the star-shaped structure, triphenylamine derivative 1, 3, 5-tris(4-diphenylamino-phenyl)benzene (TTPAB) with multiple active polymerization sites of three peripheral triphenylamine units was designed and synthesized, which was further prepared into the corresponding conjugated microporous polymer PTTPAB by chemical oxidative polymerization. The polymer PTTPAB powder exhibited the blossom sphere-like morphology with high surface area (595 m 2 /g) and plentiful micropores of the average diameter of 0.68 nm as well as mesopores of the small diameter of ∼ 2–5 nm. Being explored as the organic cathode material of battery, PTTPAB exhibited more remarkable rate performance of 84, 82, 81, 80, 84 mAh g −1 than that of PTPAn (81, 73, 72, 69, 82 mAh g −1 ) in the range of 2.5–4.2 V at current rate from 50 to 500 mA g −1 . This enhanced rate performances of PTTPAB was mainly attributed to the high specific surface area caused by the plentiful micropores and mesopores from the conjugated microporous polymer structure and blossom microspheres morphology. The high surface area can benefit to the reversible redox reaction available for Li + and shorten Li + diffusion pathway, that led to the more reduced charge transfer resistance (∼160 Ω for PTTPAB and ∼920 Ω for PTPAn), thereby improving the rate performance. Meanwhile, PTTPAB showed more stable cycling life with hardly any loss and higher coulomb efficiency during the 50th charge/discharge cycle. These excellent cell performances and unique micro-mesopores structure make PTTPAB polymer a good potential candidate as the organic cathode materials for high rate performance organic reachargeable batteries. Graphical abstract: Image 1 Highlights: We provide a realizable idea to construct CMPs by establishing star-shaped structure of triphenylamine derivatives. PTTPAB exhibits the blossom sphere-like morphology with high surface area (595 m 2 /g) and unique micro-mesoporous structure. The high surface area with plentiful micropores and mesopores can improve the rate performance as the cathode material.